My mother's son : a novel - Hirshberg, David (Bedford, New York : Fig Tree Books, 2017)
A radio raconteur revisits his childhood in post World War II Boston, sharing the everyday events his family experienced and how their lives were transformed by discoveries they never could have imagined.
Keywords: Families -- Fiction; Family life -- Fiction; Boston (Mass.) -- Fiction; Boston (Mass.) -- Fiction